Density function theory study on structures and electronic properties of 2Meq2AlOPh and its derivatives. Issue 1 (June 2015) - Ji, Yanju; Liu, Xiaocun; Fu, Gang; Chen, Ying; Wang, Fengxiang; Zhao, Junqing
Abstract: Structures and electronic properties of 2Meq2 AlOC6 H4 R (R=CN, Cl, H, OMe, NMe2 ) have been studied in the scheme of density function theory with the B3LYP and the 6-31G (d) basis set. The substitutions of the electron-withdrawing groups (CN, Cl) increase the band gap while the substitutions of the electron-donating groups (OMe, NMe2 ) decrease the gap. The substitutions of electron-withdrawing groups enhance the electron injection ability. In addition, the vertical ionization energies (IEV ), the vertical electronic affinities (EAV ) and reorganization energies of 2Meq2 AlOPh and its derivatives are calculated in the work. All complexes are better electron transport materials.